Through the Camera's Eye: Gukurahundi Genocide, Sexual Violence and Collective Trauma in Zimbabwe - Tshuma, Lungile Augustine (African studies (Johannesburg), 2025)
This paper examines traumatic memories of survivors of the Gukurahundi genocide in Zimbabwe as seen through film documentaries. While there has been a plethora of research on the Gukurahundi genocide, few studies have looked at trauma. The power of film documentaries in communicating trauma comes in that visuals can communicate a full spectrum of emotions: joy, anger, fear, disgusts, sadness, trust, surprise and anticipation. This qualitative study focuses on two documentaries the Centre for Innovation and Technology produced: I Want My Virginity Back and One Night in 1985. Findings demonstrate that these documentary films use the body as a 'geography of pain' and 'site of memory' where trauma is evoked and transmitted to the generation after. Furthermore, the next generation inherited the pain their ancestors experienced, and for that, they will pass on the information to the other generations, leading to the entrenchment of collective trauma. This study concludes by arguing that visuals, in this case being those in documentary films, give evidence of the trauma and suffering that Gukurahundi victims are experiencing. More so, the study notes that documentaries participate in the construction of trauma.